Understanding forgiveness in adolescents: the role of religiosity, self-esteem, and empathy with social support as a moderator - Susilawati, Heny; Sugiharto, DYP; Sunawan, Sunawan; Mugiarso, Heru (Jurnal Konseling dan Pendidikan, 2025)
Forgiveness is a complex psychological and spiritual process that is very important in the lives of adolescents who are full of interpersonal dynamics and the search for self-identity. This study aims to understand how religiosity, self-esteem, and empathy contribute to the tendency to forgive in adolescents, and how social support moderates this relationship. In the context of Indonesian culture, religious values are often the foundation for moral decision-making, including in the forgiveness process. High self-esteem allows adolescents to respond to interpersonal conflicts with better emotional regulation, while empathy opens up a space for understanding the motives of others that allows forgiveness to develop. This study uses a qualitative approach with a systematic literature study method, reviewing relevant scientific publications from 2013–2023 from various leading academic databases. The results of the review indicate that the three psychosocial variables—religiosity, self-esteem, and empathy—have a positive relationship with forgiveness, and this effect is strengthened by the presence of social support from family, peers, and teachers. Social support acts as a moderator that strengthens the relationship between variables by creating a sense of security, acceptance, and emotional validation that supports the forgiveness process. These findings emphasize the importance of a holistic approach and community-based interventions in developing character education programs for adolescents. This article provides a strong conceptual basis for educators, counselors, and policy makers to build strategies that support the development of forgiveness capacity among Indonesian adolescents.